Hubungan Komunikasi Dokter-Pasien dengan Kepuasan Pasien di Pelayanan Rawat Jalan - Hillery Briliani Octarina; Dini Fakhriza Alamiyah; Devita Mahajana; Antonia Alfa Yatitawi Pekey (Journal of Educational Innovation and Public Health, 2026)
The quality of interaction between physicians and patients plays a crucial role in the healthcare system, as it directly affects patient satisfaction. Ineffective communication by physicians may reduce patient satisfaction and increase the risk of complaints and medical disputes. This study aims to analyze the relationship between doctor–patient communication patterns and patient satisfaction in outpatient services. This research employed a quantitative approach with an observational analytic design using a cross-sectional method. The study population included all outpatient patients, with a sample of 110 respondents selected through accidental sampling. The independent variable was doctor–patient communication, while the dependent variable was patient satisfaction. Data were collected using a questionnaire, and analysis was performed using the Chi-Square test with a 95% confidence level. The results showed that the majority of respondents rated doctor–patient communication as good (80.9%) and reported high levels of satisfaction (75.5%). The analysis revealed that among respondents who experienced good communication, 84.3% reported high satisfaction, whereas the proportion of high satisfaction decreased significantly in the groups with moderate and poor communication. In conclusion, there is a significant relationship between the quality of doctor–patient communication and patient satisfaction in outpatient services, where improvements in communication quality are consistently associated with increased patient satisfaction.